Mutually beneficial host exploitation and ultra-biased sex ratios in quasisocial parasitoids - Tang, Xiuyun; Meng, Ling; Kapranas, Apostolos; Xu, Fuyuan; Hardy, Ian C.W.; Li, Baoping (Nature Publishing Group, 2014)
Selfish interests usually preclude resource sharing, but under some conditions collective actions enhance per capita gains. Such Allee effects underlay early explanations of social evolution but current understanding focusses on kin selection (inclusive fitness). We find an Allee effect that explains unusual quasisociality (cooperative brood care) among parasitoid wasps without invoking or precluding kin selection effects. In Sclerodermus harmandi, individual females produce most offspring when exploiting small hosts alone. However, larger hosts are more successfully exploited by larger groups of females, with the per-female benefits outweighing the costs of host sharing. Further, the extremely biased sex ratios (97% female) are better explained by mutually beneficial female–female interactions that increase the reproductive value of daughters (local resource enhancement), rather than by the usually invoked local mate competition between males. Thus, atypical quasisocial behaviour in a parasitoid wasp directly enhances reproductive success and selects for very extremely female-biased sex ratios.